In Situ Monitoring of Fiber-Reinforced Composites Theory, Basic Concepts, Methods, and Applications - Sause, Markus G.R (Springer Series in Materials Science, 2016)
"...a comprehensive and well written book, which...will be useful reading for both researchers entering the field and experienced specialists looking for new ideas....a valuable and long-lasting contribution to experimental mechanics." - Stepan Lomov, KU Leuven This expert volume, an enhanced Habilitation thesis by the head of the Materials Testing Research Group at the University of Augsburg, provides detailed coverage of a range of inspection methods for insitu characterization of fiber-reinforced composites. The failure behavior of fiber reinforced composites is a complex evolution of microscopic damage phenomena. Beyond the use of classical testing methods, the ability to monitor the progression of damage insitu offers new ways to interpret the materials failure modes. Methods covered include digital image correlation, acoustic emission, electromagnetic emission, computed tomography, thermography, shearography, and promising method combinations. For each method, the discussion includes operational principles and practical applications for quality control as well as thoughtful assessment of the method's strengths and weakness so that the reader is equipped to decide which method or methods are most appropriate in a given situation. The book includes extensive appendices covering common experimental parameters influencing comparability of acoustic emission measurements; materials properties for modeling; and an overview of terms and abbreviations. Presents a wide range of insitu, nondestructive evaluation methods Discusses a diverse set of modalities and provides detailed assessment of the pros and cons of each Combines modeling and experimental methods Includes practical applications for quality control.